Adult-Onset Kaposiform Hemangioendothelioma with Early Kasabach-Merritt Phenomenon - Yodtraiseevirat, Tinnapat; Chularojanamontri, Leena; Tuchinda, Papapit; Karoopongse, Ekapun (Thai Journal of Dermatology, 2023)
Kaposiform hemangioendothelioma (KHE) is a rare, locally aggressive, vascular tumour with a peak onset within the first year of life. The condition is extremely rare in adulthood, with fewer than 40 cases of adult KHE reported worldwide. A common feature is a single cutaneous erythematous papule, plaque, nodule or tumour with a soft tissue mass on the extremities. Extracutaneous locations such as retroperitoneum muscle, bone, and thoracic cavity can occur and lead to compressive effects or the life-threatening consumptive coagulopathy known as Kasabach-Merritt phenomenon (KMP) which has high morbidity rates. The pathogenesis of KHE involves genetic and environmental factors, the vascular endothelial growth factor-3 axis, and angiopoietin-2 signalling, resulting in dysregulation of angiogenesis and lymphangiogenesis. The diagnosis of KHE requires clinical, histopathological, haematological, and imaging information. Here, we report a case of a 59-year-old patient presented with solitary painful erythematous to purplish plaque at the left forearm for 4 months. A complete blood count showed profound thrombocytopenia (21,000 cells/mm3). Coagulogram, fibrinogen and D-dimer were within normal limits. Magnetic resonance imaging revealed mild superficial vein dilatation and subcutaneous fat in the lesion without intramuscular or deep-structure involvement. She was diagnosed with adult onset KHE with early KMP. After a discussion with haematologists, prednisolone (1 mg/kg/day) with topical tacrolimus was initiated as the patient could not afford oral sirolimus. She gradually responded, with a decrease in pain and lesion size and a normal platelet count.